Kontras Enema Sebagai Prosedur Diagnosis Hirschsprung Disease - Feggy Rizqita; Arif Zuhan (JUKEJ : Jurnal Kesehatan Jompa, 2022)
Hirschsprung's disease is a congenital disease, or present at birth, with the main signs and symptoms of constipation or intestinal obstruction, which usually appear soon after birth. Hirschsprung's disease occurs due to the absence of ganglion cells in the distal colon which results in functional inhibition in the form of failure of peristalsis to interfere with the propulsion of intestinal contents. In infants or children with Hirschsprung's disease will usually have other symptoms such as growth failure, abdominal swelling, fever and vomiting. Patients with a high index of suspicion for Hirschsprung disease should undergo a methodical diagnostic evaluation. One of the valid supporting tests for the diagnosis of Hirschsprung's disease is contrast enema (CE). Contrast enema is a widely available investigation for Hirschsprung's disease. Water-soluble contrast is enters into the colon using a catheter placed inside the anus followed by direct fluoroscopy imaging. However, the Contrast Enema procedure is avoided in patients with symptoms of enetrocolitis because of the risk of perforation. Keyword : Hirschsprung, Congenital, Diagnosis, Contrast Enema